HABBATUS SAUDA OIL-INDUCED SEVERE HYPERTRIGLYCERIDEMIA IN A PATIENT WITH DIABETES MELLITUS - Devy, M. Shandini; Ng, Ooi Chuan (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Hypertriglyceridemia (HTG) is a significant risk factor for cardiovascular disease, pancreatitis, and metabolic complications, particularly in patients with multiple comorbidities. While herbal supplements like Habbatus Sauda (Nigella sativa) oil are often used for their purported health benefits, emerging reports suggest potential adverse metabolic effects. This case highlights severe HTG potentially triggered by Habbatus Sauda oil in a patient with T2DM, dyslipidaemia and psoriatic arthritis (PsoA). CASE A 50-year-old Malay male, a research officer, presented with poorly controlled diabetes (HbA1c: 11%), dyslipidemia and severe HTG. He had a five- to six-year history of T2DM, previously on oral hypoglycemic agents (OHA) but discontinued, along with hypertension and PsoA managed with methotrexate (MTX). His triglyceride (TG) levels fluctuated significantly (2.1 → 13 → 8 mmol/L), with worsening levels temporally associated with the consumption of Habbatus Sauda oil. No other dietary or medication changes could fully explain the lipid surge. The patient was advised to discontinue Habbatus Sauda oil and implement strict lifestyle modifications. Pharmacological interventions included metformin XR, gliclazide MR, vildagliptin, dapagliflozin (self-purchased), fenofibrate and atorvastatin. Despite adherence challenges, TG levels improved from 13 mmol/L to 8 mmol/L following supplement cessation and medication optimization. Hyperkalemia (K: 6.0 mmol/L) was incidentally detected, requiring urgent potassium-lowering therapy. The patient remained resistant to injectable anti-diabetic therapy and exhibited inconsistent compliance with diet and medications. CONCLUSION This case highlights a potential link between Habbatus Sauda oil and worsening hypertriglyceridemia, underscoring the need for vigilance in patients with pre-existing metabolic disorders. While herbal supplements are widely perceived as beneficial, they may have unintended metabolic consequences, particularly in high-risk individuals. Clinicians should actively inquire about supplement use when evaluating unexplained dyslipidemia and provide comprehensive patient education on adherence and supplement safety. A multidisciplinary approach is essential to optimizing long-term cardiovascular and metabolic outcomes.